2014
DOI: 10.1097/ijg.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Early Visual Loss Following Glaucoma-filtering Surgery in Eyes With Split Fixation

Abstract: Visual loss after surgery in advanced glaucoma is rare and most often because of reversible causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…In the metaanalysis, based on eight studies, the overall effect size indicated that glaucoma surgery significantly reduces the progression velocity in glaucoma. Several studies reported an unchanged BCVA after glaucoma surgery, for both TE (Bevin et al 2008;Bhardwaj et al 2013;Balekudaru et al 2014;Bertrand et al 2014;Iverson et al 2016) and BGI (Namavari et al 2016), and in a recent randomized clinical trial (RCT) comparing primary BGI with TE (Islamaj et al 2018). This is in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the metaanalysis, based on eight studies, the overall effect size indicated that glaucoma surgery significantly reduces the progression velocity in glaucoma. Several studies reported an unchanged BCVA after glaucoma surgery, for both TE (Bevin et al 2008;Bhardwaj et al 2013;Balekudaru et al 2014;Bertrand et al 2014;Iverson et al 2016) and BGI (Namavari et al 2016), and in a recent randomized clinical trial (RCT) comparing primary BGI with TE (Islamaj et al 2018). This is in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Only a few earlier studies reported on a surgery-induced MD decline. Most studies found no influence on the MD (Tavares et al 2006;Sehi et al 2010;Yamazaki & Hayamizu 2012;Balekudaru et al 2014;Wright et al 2015;Islamaj et al 2018); one study found a deterioration of the MD after a TE (Hagiwara et al 2000). In the latter study, the postoperative MD was assessed at the end of the follow-up (mean follow-up duration was 4.75 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same report, 31 patients (7%) had late-onset hypotony (three of them with visual acuity decreased by >2 Snellen lines), and two patients developed bleb-related endophthalmitis (5) . Incidentally, another recent paper reported that visual loss after surgery, the "wipe-out" phenomenon, is rare, even in patients with advanced glaucomatous visual field loss and split fixation (6) . The Ex-Press ® implantation during glaucoma filtration surgery should be considered as a modification in trabeculectomy, and not as an entirely new procedure.…”
mentioning
confidence: 99%
“…However, the literature showed all three possible outcomes: an improvement in visual function, a decline, and no effect. (Balekudaru et al 2014, Caprioli et al 2016, Hagiwara et al 2000, Sehi et al 2010 The crucial question is, if there is a surgery-induced loss, if it counterbalances the loss avoided due to the IOP lowering. The IOP lowering aims to yield a lower rate of progression (ROP), that is, a less negative time rate of change of the standard automated perimetry (SAP) mean deviation (MD) -thus delaying blindness.…”
Section: Introductionmentioning
confidence: 99%